Prevention of carbon tetrachloride-induced liver necrosis by several amino acids. - De Toranzo, E. G. (1983)
Aspartic acid, cystine, methionine and tyrosine were protective against carbon tetrachloride (CCl4)-induced liver necrosis 24 h after its administration, when given 30 min before the hepatotoxin. Aspartic acid, cystine and tyrosine were also effective when given as late as 6 h after CCl4. The protective effects of these amino acids, however, were no longer evident when observations of CCl4-induced necrosis were made at 72 h, except for cystine, which retained its protective potential. Protective amino acid administration did not modify the concentration of CCl4 in liver, nor did it decrease the intensity of the covalent binding of CCl4 reactive metabolites to cellular constituents or the CCl4-induced lipid peroxidation. Consequently, protection cannot be attributed to modulation of these parameters. Cystine, tyrosine and aspartic acid significantly lowered body temperature of the CCl4-treated rats, while methionine did not. Combined, these results suggest that the protective effect is not attributable to lowering of body temperature in CCl4-treated animals. Protection probably results from changes in the cell response to injury promoted by amino acid administration.